2017
DOI: 10.1097/md.0000000000007042
|View full text |Cite
|
Sign up to set email alerts
|

Different surgical approaches for the treatment of adjacent segment diseases after anterior cervical fusion

Abstract: Studies in the literature have not delineated the surgical approaches of symptomatic adjacent segment diseases (ASDs) in patients undergoing reoperation after an initial anterior cervical fusion (ACF). The purpose of this study was to determine the optimal surgical approaches of ASD and the incidence of the dysphagia after reoperation.This was a retrospective study of 49 patients with ASD after an initial ACF surgery, which had undergone a reoperation at our medical center between January 2010 and December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
6
19
1
1
Order By: Relevance
“…A review of the literature, the imaging results of adjacent segmental degeneration after ACDF surgery can be as high as 92% [5,12]. and the reoperation for symptomatic ASD was ranged from 2.1-22% [5]. These results are largely in line with the studies by Hilibrand [13] and Go n [14].…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…A review of the literature, the imaging results of adjacent segmental degeneration after ACDF surgery can be as high as 92% [5,12]. and the reoperation for symptomatic ASD was ranged from 2.1-22% [5]. These results are largely in line with the studies by Hilibrand [13] and Go n [14].…”
Section: Discussionsupporting
confidence: 77%
“…ASD occurred mostly in the superior adjacent segments. Besides, Hilibrand et al found that C4/5, C5/6, and C6/7 spinal levels had a higher risk of developing symptomatic ASD than other segments [3,5,21]. A total of 22 cases (Table 1) of responsible segments were located in C4/5, C5/6, and C6/7 in the follow-up cases of this study, accounting for 84.62% of all cases.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations